Fast and Balanced Charge Transport Enabled by Solution‐Processed Metal Oxide Layers for Efficient and Stable Inverted Perovskite Solar Cells - Trystan Watson (ENERGY & ENVIRONMENTAL MATERIALS)
Metal oxide charge transport materials are preferable for realizing long-term stable and potentially low-cost perovskite solar cells (PSCs). However, due to some technical difficulties (e.g., intricate fabrication protocols, high-temperature heating process, incompatible solvents, etc.), it is still challenging to achieve efficient and reliable all-metal-oxide-based devices. Here, we developed efficient inverted PSCs (IPSCs) based on solution-processed nickel oxide (NiOx) and tin oxide (SnO2) nanoparticles, working as hole and electron transport materials respectively, enabling a fast and balanced charge transfer for photogenerated charge carriers. Through further understanding and optimizing the perovskite/metal oxide interfaces, we have realized an outstanding power conversion efficiency (PCE) of 23.5% (the bandgap of the perovskite is 1.62 eV), which is the highest efficiency among IPSCs based on all-metal-oxide charge transport materials. Thanks to these stable metal oxides and improved interface properties, ambient stability (retaining 95% of initial PCE after 1 month), thermal stability (retaining 80% of initial PCE after 2 weeks) and light stability (retaining 90% of initial PCE after 1000 hours aging) of resultant devices are enhanced significantly. In addition, owing to the low-temperature fabrication procedures of the entire device, we have obtained a PCE of over 21% for flexible IPSCs with enhanced operational stability.